1999
DOI: 10.3354/meps181097
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen transformations and factors leading to nitrite accumulation in a hypertrophic marine fish culture system

Abstract: Nitrogen transformations in a highly eutrophic model ecosystem were studied. The heterotrophic (fish and sedimentation) and autotrophic (seaweed) components of the ecosystem were separated into 3 units. The seaweed purified fish effluents from organic matter and ammonia, and enriched them with dissolved oxygen (DO). Particles were sedirnented out and the treated water was recirculated to the fish unit. Both assimilation of ammonia and production of oxidized nitrogen (ToxN) occurred mainly in the seaweed unit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 13 publications
(23 reference statements)
2
8
0
2
Order By: Relevance
“…As the temperature in the cultures increased very slightly during the system operation, the marked increase in ToxN during the study period must be related to the increase of seaweed biomass, and hence surface area. The maximum nitrification rate estimated in our study was similar to the average nitrification rate (50 mmol d −1 ) reported by Krom et al (1995) but much lower than the 240 mmol d −1 reported by Dvir et al (1999), both in a prototype integrated mariculture system involving U. lactuca. However, the net nitrification rate estimated in these studies included contributions by nitrifying bacteria growing on the walls of the algal tanks and suspended particles, which were not included in our estimation (see Methods).…”
Section: Nitrificationsupporting
confidence: 81%
See 1 more Smart Citation
“…As the temperature in the cultures increased very slightly during the system operation, the marked increase in ToxN during the study period must be related to the increase of seaweed biomass, and hence surface area. The maximum nitrification rate estimated in our study was similar to the average nitrification rate (50 mmol d −1 ) reported by Krom et al (1995) but much lower than the 240 mmol d −1 reported by Dvir et al (1999), both in a prototype integrated mariculture system involving U. lactuca. However, the net nitrification rate estimated in these studies included contributions by nitrifying bacteria growing on the walls of the algal tanks and suspended particles, which were not included in our estimation (see Methods).…”
Section: Nitrificationsupporting
confidence: 81%
“…From the comparison of ammonium uptake rates and specific nitrification rates it seems clear that, overall, the nitrifyers do not outcompete the macroalgae for the use of ammonium, as these rates represented less than 50% of the ammonium uptake rates by both macroalgal species. Krom et al (1995), and Dvir et al (1999) reached similar conclusions in an integrated culture of U. lactuca and S. aurata. Neori et al (1998) found that oxidised N was sporadically produced in their algal biofiltering tanks in small quantities.…”
Section: Nitrificationsupporting
confidence: 77%
“…After the 6th day of rotifer invasion, TAN elimination from the circuit could have resulted from nitrifying bacteria, which developed particularly in the circuit pipes (Dvir et al, 1999), as well as from opportunistic algae. We must emphasize, however, that these algae do not regulate nitrites or nitrates, the levels of which only began to decrease after Chlorella returned.…”
Section: Discussionmentioning
confidence: 99%
“…and/or Nitrospira sp., Keuter, Kruse, Lipski & Spieck, ) was not established during the 49 days of the experiment. This is probably related to the slow growth rate of these bacteria in seawater, the washout of detached particles and their associated nitrifying bacteria in this flow‐through system, and possibly also to unfavourable conditions of light and pH (Dvir, van Rijn & Neori, ). Mismatch between the two nitrification steps related to washout and other factors had been observed in freshwater‐intensive flow‐through fish culture systems with high water exchange rates (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Mismatch between the two nitrification steps related to washout and other factors had been observed in freshwater‐intensive flow‐through fish culture systems with high water exchange rates (e.g. : Diab, Kochba, Mires & Avnimelech, ; Milstein, Zoran, Kochba & Avnimelech, ) and even in stagnant fishponds flooded and washed out by heavy monsoon rains (Milstein, Wahab & Rahman, ), as well as in re‐circulating algal‐dominated warm‐water mariculture systems (Dvir et al., ).…”
Section: Resultsmentioning
confidence: 99%